Analisis Iklim Keselamatan Kerja dan Pengaruh Karakteristik Responden pada Bagian Produksi di PT. X - Shinta Silvia; Taufiq Ihsan; Ivana Azalya Rizky (Jurnal Serambi Engineering, 2020)
This study aims to analyze the work safety climate in the production section of the X Company, crumb rubber industry in Padang City. Respondents were workers in the production section which consists of managerial, wet and dry production. The workers were interviewing and filling in the questionnaire namely a questionnaire with the Nordic Occupational Safety Climate Questionnaire (NOSACQ-50) method. The NOSACQ-50 method consists of 7 dimensions, Research shows that the value of work safety climate in 7 dimensions are 3.31; 3.30; 3.17; 3.28; 2.98; 3.33 and 3.21 and has an average value of 3.23 which is a very good category on a scale of 3-4. There is one dimension, namely the fifth dimension which is still in the good category of 2.98. The characteristics of respondents include age groups, years of service, education, job titles and work sections. Each group of respondents' characteristics was proven to have an influence on work safety climate where there were significant differences in perceptions between groups. The solutions for improvement based on safety climate measurement are to increase knowledge about work safety, takes strict action to implement the use of PPE in the production area, and make periodic checks on all production equipment.